BAHAN IMPLANT TULANG BIOACIVE GLASS DARI LIMBAH AMPAS TEBU DAN LIMBAH CANGKANG TELUR : BAHAN IMPLAN TULANG KACA BIOAKTIF DARI SAMPAH TEBU DAN SAMPAH KULIT TELUR - Marwoto, Putut; Nurbaiti, Upik; Astuti, Budi; Yulianto, Agus; Nafiusokhib, Nafiusokhib; Fianti, Fianti (EduFisika: Jurnal Pendidikan Fisika, 2024)
Sugarcane bagasse and eggshell waste are common types of waste found in Indonesia. This article introduces an innovation to utilize these two waste materials as bone implant materials, offering a way to increase their economic value. Bone implant materials primarily consist of SiO2 and CaO, both of which can be derived from sugarcane bagasse and eggshell waste. The process of making bone implants begins with the purification of sugarcane bagasse and eggshell waste to produce SiO2 and CaO compounds. Characterizations conducted at each stage of the reaction process in this research include FTIR, XRD, and SEM.The purification of sugarcane bagasse into SiO2 is carried out using a hydrothermal reaction, while the purification of eggshell waste is performed using the calcination method. Once the high-purity raw materials are obtained, the process continues with the production of bioactive glass. Bioactive glass is a biomatrix material used as a bone implant material. Its composition requires SiO2 = 45%, Na2O = 25%, CaO = 25%, and P2O5 = 5% (weight/weight). The sol-gel method is employed to produce the bioactive glass.After the bioactive glass material is produced, it is further characterized to evaluate its structure and properties. Additionally, bioactivity testing is conducted using SBF (Simulated Body Fluid) to ensure its safety when used as a bone implant and its interaction with body tissues.